Elementary and Intermediate Algebra: Concepts & Applications (6th Edition)

Published by Pearson
ISBN 10: 0-32184-874-8
ISBN 13: 978-0-32184-874-1

Chapter 7 - Functions and Graphs - 7.4 The Algebra of Functions - 7.4 Exercise Set - Page 476: 21



Work Step by Step

RECALL: $(F+G)(x) = F(x) + G(x)$ Using the formula above gives: $(F+G)(x) \\= F(x)+G(x) \\=(x^2-2)+(5-x) \\=x^2-2+5-x \\=x^2-x+(-2+5) \\=x^2-x+3$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.